The The Role of Human Resource Management (HRM) in Building Industrial Relation - Vika Anjani; Agus Subianto; Rini Fatmawati (Universitas Warmadewa, 2021)
In industrial relations, the role of workers is represented by the union as a forum to voice and accommodate aspirations in the rights and obligations of workers. Meanwhile, the owners of capital are represented by human resource management (HRM), which acts as the manager of the company's assets in order to achieve ideal industrial relations. The purpose of this study is to explore the role of human resource management in fostering industrial relations. This is motivated by a violation of high work discipline, which has an impact on industrial relations involving management and trade unions. This study used a qualitative method. The data of this study consists of primary data and secondary data. The primary data are obtained from the direct interviews with related parties at PT PAL Indonesia (Persero) and the secondary data are obtained from various written sources. The results of this study showed that the management is already at the stage of cooperation, where trade unions and management work together in fostering industrial relations. This is done through the handling and resolution of employee complaints.